Metode Regresi Ridge Untuk Mengatasi Kasus Multikolinear - Ohyver, Margaretha (Bina Nusantara University, 2011)
Multicolinear is a case that occurs in multi-linear regression analysis. Using multicolinear, it will be difficult to separate the influence of each independent variable towards the response variables. It also occurs in a farm production like cabbage. To solve this problem, Ridge regression method is used. This research aims to obtain a Ridge regression model to solve the multicolinear case. By using this method, the alleged regression coefficient is obtained by variance inflation factor less than ten for six free variables.